Generation Z's Attitude to Eco Food as Determination Factor in Setting up Eco Restaurants - Denka ZLATEVA; Mariya VELEVA; Maciej DEBSKI; Antoni KOLEK (Communications of International Proceedings, 2020)
The preferences of customers in the restaurant and hospitality industry strongly depend on national characteristics, fashion and the spread of certain behavioral patterns. Therefore, it is important to reveal how the increase in the popularity of pro-ecologically oriented ideas and healthy food can affect some industries. It is sociological legitimate to select the population of people from Generation Z as a research group that is currently entering the market with new ideas and new needs. The specific aims of this paper are: (1) to explore the Generation’s Z attitude to eco food and green restaurants; (2) to conduct a comparison between representatives of Generation Z in three Middle and Eastern European countries: Poland, Bulgaria and Ukraine, concerning this attitude. The article describes the main characteristics of the Generation Z. This study presents a discussion on the results of empirical research covering the attitude of Generation Z to pro-ecological activities and lifestyle, green food and projection of consumer behavior towards the creation of green-food restaurants. The contribution of this paper is as follows: Comparative analysis was done on the basis of the answers of the representatives of Generation Z from three different post-communists countries, which has not been done till now by other authors; Innovative is the idea to outline the relation between Generation Z’s attitude to eco-food and the entrepreneurial intentions for setting-up eco-restaurants as own business; The current level of pro-ecological consciousness of the representatives of Generation Z in the three countries was revealed.
Keywords: Generation Z; pro-ecological policy; green food; eco restaurant.